Screening of New-Borns for Thyroid Status Admitted in Neonatal Ward of a Tertiary Care Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Neonatal screening program is very fruitful in saving our newborns from preventable neonatal diseases, thereby healthy grooming of future generations. Though newborn screening for a thyroid disorder is one of the greatest successes in preventive pediatrics but still has not practically worked out for all neonates in Bangladesh at the national level.The majority of newborns with a thyroid disorder have a normal appearance without detectable physical signs and are almost always missed. Screening at the proper time (Approximately 2-7 days after birth), rechecking of suspicious cases within a week, and initiation of treatment (Within 2 weeks of age) of thyroid disorders particularly Congenital Hypothyroidism (CH), can prevent the irreversible mental and physical impairments. Transient neonatal hyperthyroidism is the common form of neonatal hyperthyroidism. The purpose of the study was, Neonatal Screening (NS) to evaluate the rate of thyroid disorders among Preterm (Early preterm born before 34th week of gestation, late preterm born between 34th week and before 37th week of gestation), Term (Born within 37th to 42nd week of gestation) and Post-term (Born after 42nd week of gestation) newborns. Birth weight was alsomeasured to categorize the newborns according to their weight.Materials and methods: It was a cross-sectional, observational type of study. The place was the Neonatal Department of Chattogram Maa-O-Shishu Hospital Medical College, Chattogram. Blood samples were collected from eighty neonates aging 2 to 7 days and sent to the laboratory for estimation of TSH and FT4.Results: Total number of samples was 80. Out of them, preterm new-born were 19 and term new-born were 61, no post-term case was found. Both groups wereagain divided into normal birth weight (³2.5 kg) and low birth weight (< 2.5 kg). Hyperthyroidism (High or normal FT4 but low TSH) was observed in 23 term newborns (37.7%) and hypothyroidism (Low or normal FT4 but high TSH) in 11 term newborns (18.03%) and the rest were Euthyroid (TSH normal, FT4 normal/increased/decreased). In the case of preterm, there were more hypothyroid 03 (15.78%) than hyperthyroid 02(10.52%).Conclusion: Our study observed that, among the newborns, who were admitted to the hospital,around half of them (39 out of 80) had abnormal thyroid function. The newborns with abnormal thyroid status were informed to their parents for further evaluation by the Department of Endocrinology. It would be helpful to reach the final diagnosis and treat it accordingly.Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 44-47